PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN RETURN ON ASSETS (ROA) TERHADAP PENYALURAN KREDIT PADA PT BANK TABUNGAN PENSIUNAN NASIONAL Tbk - Jancen Roland Patty (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2018)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR) on lending and Analyze the effect of Return On Assets (ROA) on lending to PT Bank Tabungan Pensiunan Nasional Tbk, the period 2011 – 2015. This research is an empirical research, with data collection techniques used are documentation techniques. The analysis used is multiple regression analysis with the least squares equation and hypothesis testing using t-statistics to test the coefficient of partial regression and F-statistics to influence the effect together with a confidence level of 5%. The results showed that, Capital Adequacy Ratio (CAR) and Return On Assets (ROA) partially had a significant positive effect on credit distribution at PT Bank Tabungan Pensiunan Nasional Tbk.